Diversity and Enumeration of Lactic Acid Bacteria in Traditional Fermented Fish Product Bakasang from Bacan and Sanana, North Maluku - Nurmaya Papuangan; Srimaya Maswara; Hasna Ahmad; Nurhasanah Nurhasanah (JURNAL BIOEDUKASI, 2025)
Bakasang is a fermented fish product traditionally made using the viscera (internal organs) of tuna (Thunnus spp.) and skipjack tuna (Katsuwonus pelamis), with the addition of a high concentration of salt, typically around 20% or more. The fermentation process occurs naturally and spontaneously through the activity of indigenous microorganisms, particularly those belonging to the lactic acid bacteria (LAB) group. LAB are Gram-positive, catalase-negative bacteria capable of producing lactic acid, which plays a crucial role in preservation and flavor development, and also possesses potential probiotic functionality. This study aims to evaluate the diversity and population of LAB in locally produced bakasang from the Bacan and Sanana regions, as a basis for the development of functional foods utilizing local microbial resources. Enumeration and isolation of LAB were conducted using the pour plate method on de Man, Rogosa, and Sharpe (MRS) agar, followed by morphological colony characterization, Gram staining, and physiological profiling. The results showed that LAB populations in bakasang samples from both regions ranged from 10⁵ to 10⁸ CFU/g. The LAB count in bakasang from Bacan (2.4 × 10⁸ CFU/g) was higher compared to that from Sanana (4.6 × 10⁵ CFU/g). Macroscopic, microscopic, and physiological characterization of the isolates indicated similarities to the genera Lactobacillus and Lactococcus. The diversity of LAB observed in this study reflects local microbiota with promising potential to be developed as fermentation agents and probiotics for the functional food industry.